Interdisciplinary clinical target volume generation for cardiac radioablation: multicenter benchmarking for the radiosurgery for ventricular tachycardia (RAVENTA) trial - Boda-Heggemann, Judit; Blanck, Oliver; Mehrhof, Felix; Ernst, Floris; Bürgy, Daniel; Fleckenstein, Jens; Tueluemen, Erol; Krug, David; Siebert, Frank-André; Zaman, Adrian; Kluge, Anne K.; Parwani, Abdul Shokor; et al. (International journal of radiation oncology, biology, physics, 2021)
Purpose - Cardiac radioablation is a novel treatment option for therapy-refractory ventricular tachycardia (VT) ineligible for catheter ablation. Three-dimensional clinical target volume (CTV) definition is a key step, and this complex interdisciplinary procedure includes VT-substrate identification based on electroanatomical mapping (EAM) and its transfer to the planning computed tomography (PCT). Benchmarking of this process is necessary for multicenter clinical studies such as the RAVENTA trial. - Methods and Materials - For benchmarking of the RAVENTA trial, patient data (epicrisis, electrocardiogram, high-resolution EAM, contrast-enhanced cardiac computed tomography, PCT) of 3 cases were sent to 5 university centers for independent CTV generation, subsequent structure analysis, and consensus finding. VT substrates were first defined on multiple EAM screenshots/videos and manually transferred to the PCT. The generated structure characteristics were then independently analyzed (volume, localization, surface distance and conformity). After subsequent discussion, consensus structures were defined. - Results - VT substrate on the EAM showed visible variability in extent and localization for cases 1 and 2 and only minor variability for case 3. CTVs ranged from 6.7 to 22.9 cm3, 5.9 to 79.9 cm3, and 9.4 to 34.3 cm3; surface area varied from 1087 to 3285 mm2, 1077 to 9500 mm2, and 1620 to 4179 mm2, with a Hausdorff-distance of 15.7 to 39.5 mm, 23.1 to 43.5 mm, and 15.9 to 43.9 mm for cases 1 to 3, respectively. The absolute 3-dimensional center-of-mass difference was 5.8 to 28.0 mm, 8.4 to 26 mm, and 3.8 to 35.1 mm for cases 1 to 3, respectively. The entire process resulted in CTV structures with a conformity index of 0.2 to 0.83, 0.02 to 0.85, and 0.02 to 0.88 (ideal 1) with the consensus CTV as reference. - Conclusions - Multicenter efficacy endpoint assessment of cardiac radioablation for therapy-refractory VT requires consistent CTV transfer methods from the EAM to the PCT. VT substrate definition and CTVs were comparable with current clinical practice. Remarkable differences regarding the degree of agreement of the CTV definition on the EAM and the PCT were noted, indicating a loss of agreement during the transfer process between EAM and PCT. Cardiac radioablation should be performed under well-defined protocols and in clinical trials with benchmarking and consensus forming.
Gesehen am 16.12.2022